2010
DOI: 10.1524/zpch.2010.0020
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Description of Ion Conduction in Disordered Systems: From Linear to Nonlinear Response

Abstract: The modelling of the ion conduction in disordered systems is analysed from two different perspectives. First, molecular dynamics simulations are employed to extract some basic properties of the hopping dynamics. It turns out that the dynamical processes can be described to a very good approximation as vacancy hopping processes. Second, the information content of nonlinear conductivity experiments, using high electric fields, is elucidated. For this purpose the single-particle dynamics on 1D and 2D model energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…For single-particle hopping models on a lattice it is has been shown numerically that one obtains σ r < 0 for a broad box-type distribution of energies whereas a broad Gaussian energy distribution gives rise to σ r 1, in agreement with the experimental results 32 .…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…For single-particle hopping models on a lattice it is has been shown numerically that one obtains σ r < 0 for a broad box-type distribution of energies whereas a broad Gaussian energy distribution gives rise to σ r 1, in agreement with the experimental results 32 .…”
Section: Introductionsupporting
confidence: 83%
“…In previous simulations also the box-type distribution was analysed somewhat closer. It was shown that in this case one observes σ r < 1 32 . When mapping this distribution on a bimodal distribution an appropriate choice is α ≈ 1/2.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…[14][15][16][17][18] Other models predict positive third-order a) Email: laxminar@chemie.uni-marburg.de dc conductivity coefficients, which are, however, much smaller than those found in experiments. 19,20 The frequency dependence of the third-order conductivity spectra of solid ion conductors differs clearly from the universal dynamic response observed in the linear spectra. At low frequencies, a dc plateau regime is detectable in the third-order spectra.…”
Section: Introductionmentioning
confidence: 95%
“…Interestingly, for periodic boundary conditions the conductivity displays nonanalytic behavior at zero field in the thermodynamic limit [7,24]. From studying a disordered discrete 3D-energy landscape via computer simulations it turned out that for a Gaussian distribution of site energies the experimental relation a app a hopp can be recovered [25].…”
Section: Via the Relationmentioning
confidence: 99%